The synthesis and photochemistry of some 3-phenylenones - Seery, Michael (Trinity College (Dublin, Ireland). School of Chemistry, 2003)
The excited triplet state of 3-phenylcyclohexenone has been studied by laser flash photolysis and time-resolved infrared spectroscopy. Laser flash photolysis has been used to determine rate constants of decay of excited state and quenching by ground state. The excited state absorption spectrum was obtained, giving a broad maximum similar to that found for other enones. Time-resolved infrared spectroscopy has been used to obtain an infrared spectrum of the excited state, showing a reduction in frequency of the carbonyl bond strength. In addition, the shift of the carbonyl from ground to excited state indicates the excited state is π,π* in character, a result previously determined by phosphorescence. In addition to studying 3- phenylcyclohexenone, the enone was examined in the presence of E-1-phenylpropene quencher. Laser flash photolysis was used to calculate rate constants for quenching by the alkene. Time resolved infrared spectroscopy was used to obtain a spectrum of the excited state and investigate the presence of any other intermediates in the enone-alkene cycloaddition reaction. A new group of enones was also synthesised - all having the 3-phenylenone backbone. Various methods of synthesising these molecules were attempted, and the most useful routes are described. These molecules are designed so that they are synthetic precursors to the photo-therapeutic drug psoralen. They have an active site for [2+2] addition to simple alkenes or to thymine in DNA. Some crystal structures were obtained showing an essentially planar molecule with the phenyl substituent at an angle to the plane. This indicates that these molecules may be useful as photoactive intercalators, in a manner similar to psoralen. The reaction of 6-methoxy-3-phenylindenone with E-1-phenylpropene was examined in both deutero acetonitrile and benzene. The reactions were followed by NMR. It was found that dimerisation of the enone is overwhelmingly favourable, a fact attributed to efficient π-stacking of the enone molecules in solution. Some adduct formation with the alkene was observed in benzene, but sufficient quantities could not be formed for further analysis. Computer modelling of the molecule shows that π-stacking can be a favourable process, as the barrier for rotation of the phenyl group is relatively small.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin